Las relaciones familiares y el rendimiento escolar de los niños del séptimo año de educación básica de la escuela “Dr. Luis Felipe Zapater Álvarez Blanco” de la ciudad de Loja. Periodo julio 2013 - mayo 2014 - Alvarado Jaya, Inés Paulina (2014)
This thesis refers to: FAMILY RELATIONSHIPS AND SCHOOL PERFORMANCE OF THE CHILDREN OF THE SEVENTH YEAR OF BASIC EDUCATION SCHOOL "DR. LUIS FELIPE ALVAREZ ZAPATER WHITE "CITY OF LOJA. PERIOD JULY 2013 - MAY 2014, whose purpose was: Knowing how family relationships affect school performance of children. To carry out this study the Scientific, Analytical, Synthetic, they that were of great help in the effective achievement of my research work method was used. The techniques and instruments used were: a survey of teachers and parents, the test Saks applied to children seventh year of basic education; another method used is descriptive method used throughout the research process and of course the essential statistical method in research to quantitatively measure the results of surveys and test Saks applied; tools and methods which as I have said were essential to learn and deepen my research topic. It is important to add the collaboration of 32 children / as, 3 teachers and 32 parents intrinsic part of the investigation. In analyzing the results of the test Saks family area 25% of children do not conflict or difficulty in their family relationships being this good for comprehensive development in children, another percentage of 44% of the students present conflict or slight difficulty being these negative results for their integral development, 31% have a well-defined conflict or severe difficulty, which is a worrying situation because children are constantly going through situations of conflict and even harsher which influences greatly in their development in the aspects of your life, emotional, self-esteem, academic, and more. Similarly to the results of the survey of teachers have been able to demonstrate poor academic performance, 67% of children have a low academic performance is grade level barely learning required, this being a worrying situation which is conjugated to the family area. Therefore academic performance is worrying that present school this is due to the conflicts they pose in their family relationships so troubled and distant. Among its features are rooted economic factors, lack of communication, use of alcohol and drugs. Pun these factors have a direct bearing on the level of educational achievement of children in the seventh year of basic education in the School Dr. Luis Felipe Blanco Zapater city of Loja, since they exhibit a low level of performance, is barely learning required.